Detrital zircon U-Pb geochronology of sediments from the Okinawa Trough: implications for sedimentary provenance - Yang, Bao-Ju; Liu, Ji-Hua; Wu, Yong-Hua (Frontiers in Earth Science, 2024)
In order to distinguish terrestrial material sources in the Okinawa Trough (OT), this study analyzed four surface sediment samples from the northern, middle, and southern parts of the OT using detrital zircon U-Pb age analysis. The detrital zircon age distributions in the northern Okinawa Trough (N-OT) predominantly fall into 1,000−2,300 Ma and 100−600 Ma age groups. In contrast, in the middle Okinawa Trough (M-OT) and southern Okinawa Trough (S-OT), the detrital zircon age groups of 100−600 Ma and 600–1,000 Ma increase significantly, while the age groups of 1,000−2,300 Ma and >2,300 Ma decrease. Detrital zircons from the N-OT primarily originate from the Yellow River and mixed with the Old Yellow River, while those from the M-OT come mainly from the Yellow River, Yangtze Rivers, and East China Sea. And Zhuoshui River maybe a potential source for the M-OT. The detrital zircons from the S-OT are mainly influenced by the Yangtze River, with some effects from the Lanyang River. This study utilizes detrital zircon U-Pb age analysis to gain a better understanding of the terrestrial material sources in various regions of the OT. Most of the zircon grain are coarse, with grain sizes of 40–150 μm long and 30–100 μm wide in the N-OT, smaller in the M-OT and S-OT in this study, which are probably not modern deposits, but the products in the low sea level period of last glaciation mixed with modern sediments. The transport and sedimentation processes reflect the comprehensive influence of sea level change, Kuroshio Current, river input, East Asian monsoon and other factors from last glaciation to present.